PENGAPLIKASIAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES DAN EFEKNYA TERHADAP KETERAMPILAN MENULIS PUISI SISWA SEKOLAH DASAR - Pattiasina, Petrus Jacob; Sutarto; Al Padli; Oci, Markus; Handayani, Linda; Sanulita, Henny (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Writing skills are very important for students, but basically writing skills in schools are still low and are always underestimated by students and educators. Everyone can write and there is no need to focus on writing skills. Therefore, writing learning activities in educational units do not run as expected. During writing learning activities, students find it difficult to focus and students are less motivated to do writing activities. This explanation is because students do not get enough impact in learning to write and students assume that learning Indonesian is easy. The research carried out aims to review the impact of the non-example model on poetry writing skills in class V SD Negeri 1 Latihan SPG Ambon. This research uses a quantitative approach in the form of experiments. Based on the research that has been carried out, it was found that the results of applying the non-example model to poetry writing skills in class V SD Negeri 1 Latihan SPG Ambon. This is proven by the results of the t test with a significance level of 5%, obtained t-table 2.01 while t-count = 15.98, because learning using pictures is sequenced logically which can open students' schemes and ensure students understand the learning presented with the help of media. visuals, students are also stronger in memorizing and reading by connecting using images.